2021
DOI: 10.1080/2162402x.2020.1865653
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab as a monotherapy or in combination with platinum-based chemotherapy in advanced non-small cell lung cancer with PD-L1 tumor proportion score (TPS) ≥50%: real-world data

Abstract: Both pembrolizumab (P) and combination of pembrolizumab with platinum-based chemotherapy (PCT) represent standard 1 st -line options for advanced non-small cell lung cancer (aNSCLC) with PD-L1 tumor proportion score (TPS) ≥50%. The two strategies have never been compared in a randomized trial. 256 consecutive patients with EGFR/ALK/ROS1-wild-type PD-L1 TPS ≥50% aNSCLC receiving P (group P, n = 203) or PCT (group PCT, n = 53) as a 1 st -line treatment were identified in the electronic databases of 4 Israeli can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Dudnik et al. ( 32 ) reported median OS of 20.4 months (95% CI, 10.8-not reached) for 53 patients, most with good performance status (85% ECOG PS 0–1), with EGFR/ALK/ROS1 -wild-type advanced NSCLC, PD-L1 ≥50% who received first-line ICI plus platinum-based chemotherapy at Israeli cancer centers. In another retrospective non-US study (at the Shanghai Chest Hospital), median OS was not reached for 115 patients with advanced NSCLC (both nonsquamous and squamous), PD-L1 ≥50%, and no EGFR or ALK genomic alterations who received first-line pembrolizumab-chemotherapy ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dudnik et al. ( 32 ) reported median OS of 20.4 months (95% CI, 10.8-not reached) for 53 patients, most with good performance status (85% ECOG PS 0–1), with EGFR/ALK/ROS1 -wild-type advanced NSCLC, PD-L1 ≥50% who received first-line ICI plus platinum-based chemotherapy at Israeli cancer centers. In another retrospective non-US study (at the Shanghai Chest Hospital), median OS was not reached for 115 patients with advanced NSCLC (both nonsquamous and squamous), PD-L1 ≥50%, and no EGFR or ALK genomic alterations who received first-line pembrolizumab-chemotherapy ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the 4-year follow-up data of the KEYNOTE-189 trial, the 3-year survival rate of the TPS high population was 43.7% [ 5 ], which is comparable with the 3-year survival rate (43.7%) in the analysis of the 5-year follow-up data of the KEYNOTE-024 trial [ 6 ]. There are other two reports used real-world data; however, the trend was similar [ 7 , 8 ]. The significance of combining chemotherapy is not clear when comparing these results.…”
Section: Introductionmentioning
confidence: 83%
“…Though seemingly at odds with previously published randomized clinical trial (RCT) results, the duration of mOS observed on ICI therapy here is consistent with other real-world studies. [28][29][30] Moreover, it is worth noting that this is a summary result rather than a direct comparison between therapies, and could be due to the observational nature of this trial, the fact that patients were not randomized but rather therapy was decided by their physicians based on a multitude of factors including HIC results, 31 changes in treatment paradigms over the course of the study, and the inclusion of a heterogeneous real-world patient population often excluded from RCTs.…”
Section: Discussionmentioning
confidence: 99%